Global introductions and environmental impacts of freshwater megafish - Xing Chen; Thomas G. Evans; Jonathan M. Jeschke; Sonja C. Jähnig; Fengzhi He (Global Change Biology, 2024)
Freshwater megafish species, such as sturgeons, salmonids, carps, and catfishes, have a maximum reported weight ≥30 kg. Due to their charisma and economic value, they have been widely introduced outside of their native ranges. Here, we provide a comprehensive overview of the introduction of freshwater megafish and an assessment of their environmental impacts. Of the 134 extant freshwater megafish species, 46% have been introduced to new environments, and of these, 69% have established self‐sustaining alien populations. These introductions affect 59% of the world's main basins, with the USA and western Europe being particular hotspots of megafish introductions. The common carp ( Cyprinus carpio ) is the most widely introduced species. Using the Environmental Impact Classification for Alien Taxa (EICAT and EICAT+) frameworks, we assessed the severity and type of negative and positive impacts posed by alien megafish on native species. Alien megafish caused negative impacts through nine different mechanisms, with predation being the most frequently reported mechanism, followed by herbivory and competition. Moreover, 58% of the alien megafish species with sufficient data to evaluate the severity of their impacts caused declining populations of native species, or worse, extirpations of native species populations. The positive environmental impacts of alien megafish were far less frequently documented. They include biotic interactions that benefit native species, and the provision of trophic resources or habitats. Widely introduced or extensively studied species are more likely to have documented severe impacts on native species. There is a clear trade‐off between the economic benefits associated with megafish introductions and the severe adverse impacts they have on native biodiversity. Our study highlights the need for comprehensive risk assessments to evaluate the potential environmental impacts of megafish. More research and long‐term monitoring schemes are required to inform management actions to protect biodiversity, particularly in the Global South.